Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1266/jjg.64.209
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype evolution in the social wasps (Hymenoptera, Vespidae).

Abstract: The chromosomes of 21 species of Vespidae (consisting of 9 polistines and 12 vespines) were compared using an air-drying technique.The haploid number of the Polistinae ranged broadly (n=14, 22, 23, 26, 30, 31, and 34), while it was either n=25 or n=26 in the Vespinae. There were no karyological homologies (in terms of marker chromosomes) between these two subfamilies. Some phylogenetic relationships of social wasps were discussed, based on the karyological literature now available (32 species). We suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Although important in the process of heterochromatin elimination from the pseudoacrocentric chromosomes, this type of rearrangement is considered rare in the evolution of animal karyotypes (White, 1973). It was nevertheless observed by Imai et al (1994) in ant species of the Myrmecia pilosula complex, and was also identified in wasps of the genus Vespula by Hoshiba et al (1989) as one of the events in metacentric chromosome formation, by which pair 1A also seems to have been formed. However, in order to achieve greater karyotype stability, this pair of chromosomes may still be undergoing fission, as demonstrated by the one-armed heteromorphism pattern that, according to Imai et al (1994), is characteristic of this kind of rearrangement.…”
Section: Discussionmentioning
confidence: 79%
“…Although important in the process of heterochromatin elimination from the pseudoacrocentric chromosomes, this type of rearrangement is considered rare in the evolution of animal karyotypes (White, 1973). It was nevertheless observed by Imai et al (1994) in ant species of the Myrmecia pilosula complex, and was also identified in wasps of the genus Vespula by Hoshiba et al (1989) as one of the events in metacentric chromosome formation, by which pair 1A also seems to have been formed. However, in order to achieve greater karyotype stability, this pair of chromosomes may still be undergoing fission, as demonstrated by the one-armed heteromorphism pattern that, according to Imai et al (1994), is characteristic of this kind of rearrangement.…”
Section: Discussionmentioning
confidence: 79%
“…For the chromosome counts, the reproductive organs from the last larval stage or from young pupa of both sexes were generally used. The chromosome preparations were made by lactic acid dissociation, a drying technique improved by Hoshiba et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…It is of some interest that both mammals and ants exhibit an extremely wide range of chromosome number variation: 2n--6-92, and 2n--2-94 respectively (for details see Imai, 1988;and Hoshiba et al, 1989).…”
Section: Resultsmentioning
confidence: 99%